Alcohol use during pregnancy: the impact of social determinants of health on alcohol consumption among pregnant women - MacKenzie R. Peltier; Terril L. Verplaetse; Vera Bici; Abbie A. Mokwuah; C. Leonard Jimenez Chavez; Yasmin Zakiniaeiz; Robert Kohler; Vernon Garcia-Rivas; Bubu A. Banini; Hang Zhou; Nakul R. Raval; Brian Pittman; et al. (Biology of Sex Differences)
Abstract Background There is no safe amount or time of alcohol consumption during pregnancy; however, many women drink while pregnant placing themselves and their fetuses at risk for alcohol-related health complications. Social Determinants of Health (SDoH) impact alcohol use during pregnancy. Understanding the impact of SDoH across pregnancy will elucidate important information to reduce rates of prenatal alcohol exposure. Methods Cross-sectional data from the National Survey of Drug Use and Health from 2009 to 2019 was used to explore the impact of SDoH on alcohol use across pregnancy. The study assesses past month alcohol use and past month binge drinking, as well as various SDoH. The sample included 8,638 pregnant women. Results Over 9% of pregnant women reported alcohol use within the past 30 days and 5.25% reported drinking on three or more days within the past month. 3.65% reported past month binge drinking. Past month alcohol use and past month binge drinking decreased in the second and third trimesters; however, a subset of women continued alcohol use, including binge drinking. Specific SDoH emerged as increasing the likelihood of alcohol use within the past month, including not being married (ORs = 1.54 to 1.94), criminal justice involvement (arrested and booked; OR = 1.88), and past year psychiatric distress (OR = 1.86). Conversely, other determinants were associated with a lower likelihood of alcohol use, including identifying as Asian or Hispanic (ORs = 0.41 and 0.64) and unemployment (OR = 0.52) and other employment (OR = 0.66). Older age was associated with a lower likelihood of binge drinking within the past month (ORs = 0.32). Unique SDoH emerged when examining alcohol use by trimester. Conclusion Specific SDoH (i.e., not married, criminal justice involvement, past year psychiatric distress) are related to increased alcohol use during pregnancy, while other determinants (i.e., identifying as Asian or Hispanic, not requiring full time/part-time employment) are associated with a decreased risk for past month alcohol use. Older individuals (35–49 years old) and those with a high school education had a decreased likelihood of binge drinking. Accordingly, healthcare providers should screen all pregnant women for alcohol use throughout pregnancy, especially among populations or groups identified as being vulnerable to continue alcohol use during pregnancy.